Tracer test and design optimization of doublet system of carbonate geothermal reservoirs. (November 2022) - Liu, Yanguang; Long, Xiting; Liu, Fei
Highlights: A doublet system was selected to carry out reinjection tracer test with sodium naphthalenesulfonate as the tracer. 1D and 3D models were established to simulate and optimize the multiple exploitation-reinjection schemes. A dominant fissure channel with a length of 513.7 m was shown between the exploitation well and reinjection well. Abstract: The imbalance between large-scale exploitation and reinjection year by year has led to the decline of the water level of the geothermal reservoirs in the North of China. The reinjection tracer test was carry out based on the doublet system in the Xianxian geothermal field in China with sodium naphthalene sulfonate as the tracer in this paper. The 1D and 3D models were modeled on the software COMSOL in this study to simulate the predictive analysis of multiple exploitation-reinjection schemes and optimize the design. The monitoring data of the tracer concentration in the water samples collected at the wellhead of the exploitation well showed that the tracer was firstly detected on 30th days after the tracer test started. Afterwards, the tracer concentration reached a peak on the 100th day and then gradually decreased until ∼ 140th day, with a tracer recovery rate of 0.0225%. And one dominant fissure channel between the exploitation well and reinjection well with a length of ∼ 513.7 m was shown in the test. The thermal breakthrough time of the exploitation well was defined as the time when the temperature decreases by 2 °C after 100 years of geothermal exploitation. Based on this, the optimal exploitation solution of the geothermal resources was proposed as the spacing between the exploitation well and reinjection well should be set as ∼ 375 m and the exploitation and reinjection volume is 75 m 3 /h.